Burden of injuries and its associated hospitalization expenditure in India. Issue 2 (3rd April 2021) - Yadav, Jeetendra; Menon, Geetha; Agarwal, Amit; John, Denny
Abstract: Injuries are a major public health concern, affect the most productive age group i.e. (15–60 years) and increases disability adjusted life years (DALYs) and results in a huge financial burden on the household. Disease burden is represented by DALYs and economic burden represents the out of pocket (OOP) and catastrophic health expenditure (CHE). We examined the burden of injury and its impact on household financial burden among the working population (15–60 years) in India. We used data on National and State Level DALYs for Injuries for 2017 from the published National Disease Burden Estimate (NBE, 2019) Study. The cost of treatment was extracted from 75th round of the National Sample Survey Organization (NSSO, 2017–18). DALYs is the sum of YLLs and YLDs. OOPEs were estimated as a per episode of hospitalization expenses after reimbursement and CHE was defined as out of pocket expenditure exceeding 10% of household consumption expenditure. Accidental injuries particularly road traffic injuries have higher DALY rates among 15–60 years in India (1288 DALYs per 100, 000). However, the mean OOPE was found to be higher due to intentional self-harm. Persons suffering from injury in states like Punjab, Haryana, UP, Gujarat, Karnataka and Andhra Pradesh approached private facilities more compared to public facilities. Whereas, people from states like Jammu and Kashmir, Orissa, West Bengal, North East availed public facilities more than private. OOPE was found to be five times more in private facilities than in public. The households who sought treatment in private facilities were faced 3 times more to Catastrophic expenditure than those who took the treatment in public hospital of any injury. The present study indicated high DALYs, OOPE and % CHE for injury in India. Higher proportion of households were pushed to catastrophic expenditure due to high OOPE of injury treatment. Disease and economic burden due to road traffic injury and fall was found to be high as compared to other injuries. Our study strengthens the need for executing effective financial protection approach in India like PM-JAY, to minimize the financial burden incurred due to injuries in India.